2021
DOI: 10.14260/jemds/2021/352
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Occupational Therapy among People in Saudi Arabia

Abstract: BACKGROUND The public awareness about occupational therapy and its role is not much studied in Saudi Arabia. Therefore, this study intended to provide baseline data about existing knowledge, as well as to identify the knowledge gaps in specific domains of knowledge which could help in designing precise and targeted strategies to increase awareness about the occupational therapy (OT) services, their role, and scope among the masses. METHODS A cross-sectional survey was carried out among people of Saudi Arabia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In fact, this may also result in shorter length of stay and reduced postoperative costs. 50 This is particularly important given that the limited time and resources occupational therapists have with such conditions combined with the lack of awareness of occupational therapy 51 may reduce the number of times an occupational therapist can see a lower extremity joint replacement patient prior to their surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this may also result in shorter length of stay and reduced postoperative costs. 50 This is particularly important given that the limited time and resources occupational therapists have with such conditions combined with the lack of awareness of occupational therapy 51 may reduce the number of times an occupational therapist can see a lower extremity joint replacement patient prior to their surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey asking 4,440 people in Saudi Arabia about their knowledge of OT found that the general public also did not understand the role of OT and its services [ 61 ]. In addition, a cross-sectional study compared the knowledge of OT and physiotherapy services between healthcare professionals and the public in Saudi Arabia [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, OTs in Saudi Arabia abide only by the codes of conduct issued by regulatory, licensing, and registration bodies, such as the SCFHS [ 29 ]. Since these guidelines can be multi- or interdisciplinary, this can result in confusion regarding how the role of an OT specialist differs from that of other rehabilitation specialities, which may have similar and related aims [ 61 ]. Moreover, physiotherapists or special-education specialists who receive 40 hours of OT training can work as OT professionals in day-care centres for people with disabilities, as established in a policy issued by the Ministry of Labour and Social Development [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general lack of knowledge and awareness about OT. 1,2 The profession had been described as vague among the public, 1,3 and average at best amongst healthcare workers. 1,4,5 The level of knowledge of clients about OT affects their expectations and acceptance of OT services.…”
Section: Introductionmentioning
confidence: 99%